Povstání z pokleku: Pražské bohoslužby v šedesátých letech 20. století III. - Procházková, Zora; David, Jan; Nešpor (ed.), Zdeněk R. (Lidé města, 2022)
Academic edition of an exceptional source depicting (records from) observations of Prague Christian churches’ services in the mid-1960s, supplemented with a contextualizing introduction and historico-religious footnotes by the editor. The specificity of the material is that the original source takes the form of (commented) participatory observation, it is very open and at the same time it contains material from (almost) all existing churches and religious societies, respectively individual parishes, congregations and places of worship in the city of Prague. Due to its length is the edition divided into several parts; this third part contains the first part of Roman Catholic worships (churches A–N).